2009
DOI: 10.1161/strokeaha.109.547547
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Transcranial Laser Therapy for Acute Ischemic Stroke

Abstract: MD; for the NEST-2 InvestigatorsBackground and Purpose-We hypothesized that transcranial laser therapy (TLT) can use near-infrared laser technology to treat acute ischemic stroke. The NeuroThera Effectiveness and Safety Trial-2 (NEST-2) tested the safety and efficacy of TLT in acute ischemic stroke. Methods-This double-blind, randomized study compared TLT treatment to sham control. Patients receiving tissue plasminogen activator and patients with evidence of hemorrhagic infarct were excluded. The primary effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
203
0
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(231 citation statements)
references
References 13 publications
4
203
0
22
Order By: Relevance
“…In rabbits, it has been estimated that NIr from a laser device may reach a depth of 25-30 mm from the cortical surface, 21 while a similar estimate of approximately 20 mm has been predicted in humans. 47 However, there would be considerable attenuation and loss of power intensity from the cranial surface and through the brain parenchyma. Shaw and colleagues 38 have suggested that in mice, there is an approximately 90% decline in the NIr signal inside the cranium after external application via a light-emitting diode (LED).…”
mentioning
confidence: 99%
“…In rabbits, it has been estimated that NIr from a laser device may reach a depth of 25-30 mm from the cortical surface, 21 while a similar estimate of approximately 20 mm has been predicted in humans. 47 However, there would be considerable attenuation and loss of power intensity from the cranial surface and through the brain parenchyma. Shaw and colleagues 38 have suggested that in mice, there is an approximately 90% decline in the NIr signal inside the cranium after external application via a light-emitting diode (LED).…”
mentioning
confidence: 99%
“…[8,14] Positive sham-controlled studies in acute stroke patients included the single T-LLT stimulation of 20 points according to the 10-20 system for one minute each, the wave length was 808 nm and the intensity 10 mW/cm 2 . [15,16,17] In embolized rabbit's brain, Lapchak and De Taboada successfully showed that T-LLT (wave length 808 nm, intensity 10 mW/cm 2 ) significantly increased the cortical ATP, the penetration depth was 20 -30 mm. [18] Accordingly the authors of the acute stroke studies speculated that the transcranial laser could have activated the respiratory chain, namely the complex IV, thus increasing the ATP production and helping cell recuperation.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The exclusive frontal application followed the previous clinical reports on the beneficial effects of N-LLT. [15,20] Further N-LLT was assumed to improve the cell metabolism of the stimulated brain areas. In the tDCS trials, the authors stimulated the left dorsolateral prefrontal cortex (DLPF) which is said to receive visual and and somatosensory input from the parietal heteromodal association cortices regarding vision, motion, spatial orientation and tactile sensations, and projects to subcortical monoaminergic and cholinergic sources.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusive frontal application followed the previous clinical reports on the beneficial effects of N-LLT [15,20]. Further N-LLT was assumed to improve the cell metabolism of the stimulated brain areas.…”
Section: Care Wheel Chairmentioning
confidence: 98%
“…With the transfrontal application one should keep in mind the variable size of the frontal sinus, the bone around the sinus is thicker, and not seldom a sinusitis affects severely affected chronic patients. A thick bone and fluid, however, decrease the Positive sham-controlled studies in acute stroke patients included the single T-LLT stimulation of 20 points according to the 10-20 system for one minute each, the wave length was 808 nm and the intensity 10 mW/cm 2 [15][16][17]. In embolized rabbit's brain, Lapchak and De Taboada successfully showed that T-LLT (wave length 808 nm, intensity 10 mW/cm 2 ) significantly increased the cortical ATP, the penetration depth was 20-30 mm [18].…”
Section: Care Wheelchairmentioning
confidence: 99%